Proyecto de factibilidad para la Implementación de una empresa de alquiler de bicicletas para la Ciudad de Loja - Castillo Ojeda, Lina Patricia (2015)
The subject-matter exhibited in the present work takes as a main target to realize the practicality study for the implementation of a company of rent of bicycles for the city of Loja. The structure of the present thesis is developed as it is detailed next: a) This literal refers to the title of this work: "Project feasibility for the implementation of a company of rent of bicycles for the city of Loja" b) .Below is a summary which includes the methods and techniques used, as well as detailed results of greater relevance c) In the introduction, is an analysis of the theme at a general level ((, in addition, detailed studies that comprise the present thesis d) In the review of literature cited bibliographic content referring to the feasibility study and the subject expect. e) Details the methods and techniques used. The deductive method, through which the subject could analyze generally for deepening of the particular to one's own, know the incidence of this means of transport at the national and local levels. The inductive method allowed record facts, analyze them and reach a general idea of the environment, through newspaper articles, details of the acceptance of motivation for cycling events organized by the Town Hall, etc. Through the statistical method was given treatment to data from 400 surveys applied to supply and demand. In relation to the applied techniques was the interview people related to cycling in Loja, as well as for the proposal of the Council on the issue. f) This literal presents the results after the polls the population economically active city of Loja and the suppliers of the service. g) In this literal is the discussion, which is necessary to perform each of the studies comprising the project's feasibility. Market study revealed the unsatisfied offer for the service, which is located in 1488274 in the first year, then is defined the Marketing Plan, which makes reference to the product, price, square and advertising that will have the bike rental service. Then, was the technical study in which you define installed and used capacity that will take the company, proposing that they will work to a 95% of its capacity and will provide 407550 services a year. Then analyzes the location factors and defines the location in the city of Loja. With regard to the engineering of the project, processes is required to carry out for the benefit of the service and is the corresponding flowchart graph. In the technical study also he is the organizational study for the project, after an analysis of the Constitution of companies regulations, you select the type of society and is drawn up its legal base, becoming "Loja Bike Company limited". Subsequently, is the administrative organization, noting the staff required, hierarchical levels, organizational charts and manual functions. The economic study details all investments in deferred, fixed assets and working capital needed by the company to start operations, whose initial investment stood at 129115,88 U.S. dollars which will be provided by three members of the company and 46% 54% remaining by banking credit. In the financial evaluation, by means of indicators is known the profitability of the project, with the following results: the VAN is 14306, 38 which indicates that the project is viable. The IRR is located at 19.25%, which is higher than the opportunity cost of money and indicates that the project is acceptable. The cost benefit relationship reveals that for every dollar invested, you will get a profit of 0.25 cents. Capital recovery time is 3 years 6 months 17 days. The sensitivity analysis suggests economic scenarios complicated, was obtained so that the project is profitable even with a rise in costs of 3.07% and a decrease in revenues of 2.46%. It is important to indicate that all the calculations have been carried out for a project 5-year. h) Once each of the stages comprising the feasibility study in this literal presents the conclusions. i) And recommendations it is suggested to check the number of bikes to acquire and can gradually increase the fleet in order to reduce the value of the initial investment, in addition to reviewing the rental from the 2 year price for greater profitability. j) In this literal are annexes to the job, such as surveys, copy of the approved project format